BASIC CONCEPTS OF STUDYING DESIGN AND FASHION LANGUAGE TERMS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article discusses the concept of translating terms in the field of design and fashion, also, the concept of fashion was considered from the points of view of various humanities referring to the historical and chronological aspects, was discussed the main scientific theories of fashion, which have the status of classical ones.